The influence of postoperative complications on long-term prognosis in patients with colorectal carcinoma - Beck, Clemens; Weber, Klaus; Brunner, Maximilian; Agaimy, Abbas; Semrau, Sabine; Grützmann, Robert; Schellerer, Vera; Merkel, Susanne (International Journal of Colorectal Disease, 2020)
Background: The impact of postoperative complications (POCs) on the long-term prognosis of patients with colorectal carcinoma was analysed with respect to their severity according to the Clavien-Dindo classification (CDC). Methods: The prospectively collected data of 2158 patients who underwent curative resection of a colorectal carcinoma (1168 rectal carcinomas, 990 colon carcinomas) without distant metastases from 1995 to 2014 were analysed. The POCs were documented in a standardized form and graded with the CDC. Patients who died postoperatively (CDC grade V, 1.7%) were excluded. Results: In total, 467 patients (21.6%) had POCs: CDC I, 141 (6.5%); CDC II, 162 (7.5%); CDC III, 112 (5.2%); and CDC IV, 52 (2.4%). More POCs and higher CDC grades were found in men, ASA III-IV patients, rectal carcinoma patients, and patients who underwent abdominoperineal excisions or multivisceral resections. The 5-year locoregional recurrence rate was 5.3% in patients without POCs and 6.6% in patients with POCs. It was highest in CDC III patients (12.9%), which was confirmed in multivariate analysis (HR 2.2; p = 0.005). The 5-year distant metastasis rate was 15.9% in CDC 0 patients and 19.5% in CDC I–IV patients. In multivariate analysis, distant metastasis was highest in CDC III patients (HR 1.7; p = 0.020). The 5-year overall survival rate was 83.5% in patients without POCs and 73.5% in patients with POCs. It was worst in CDC IV patients (63.1%), which was confirmed by multivariate analysis (HR 1.9; p = 0.001). Conclusion: Patients with POCs after colorectal surgery have a poor long-term prognosis. As the CDC grade increases, survival deteriorates.
CRIS-Team Scopus Importer:2020-04-14
Keywords: Clavien-Dindo classification; Colorectal carcinoma; Postoperative complications; Prognosis